Increasing Recognition of Fetal Heart Anatomy Using Online Tutorials and Mastery Learning Compared With Classroom Instructional Methods. (March 2014) - Scott, Ted Edward; Thomas, Laura; Edwards, Keith; Jones, Judy; Swan, Hans; Wessels, Andrew
Assessment of the fetal heart is a challenging part of any routine obstetrical sonogram. The practice of teaching and learning this skill demands expertise in the visualization and interpretation of normal sonographic appearances of the fetal heart. Recognition of the pathological features associated with commonly seen congenital heart diseases is also very important. In the study reported here, students in an obstetrical sonography course were randomly assigned to two groups. The students in the control group (classroom instruction) on average assessed correctly all five anatomic cardiac features but determined the normal or abnormal status of only 19% of cases, 4.7of 25 ± 4.4 SD. The experimental group (online tutorials) correctly identified 39% of cases, 9.9 of 25 ± 2.7 SD, P < .01. The average score in the experimental group was greater than 84% of the students in the control group, a one sigma effect. These data support the conclusion that students learning to assess the fetal heart for the presence of congenital heart disease using a series of online tutorials and practice exercises compared with students receiving conventional classroom instruction demonstrated an improved ability to correctly identify normal and abnormal fetal heart structures.